Negara dan Monopoli Alamiah serta Perkembangan di Indonesia - Anggoro, Teddy (Jurnal Hukum & Pembangunan, 2023)
Natural monopoly is a controversial theory to be developed or implemented in today's world. It is important to note that every time an economic crisis hits the world, at that time natural monopoly loses its popularity, because it is the party to blame for the economic crisis that occurs, especially if the natural monopoly is held by State-Owned Enterprises (BUMN). Indonesia is one of the countries that through the BUMN Law prohibits natural monopoly on certain industries to be applied. This becomes important to study considering that natural monopoly itself is a way to achieve efficiency, such as the goal of business competition. On the other hand, natural monopoly itself is one way for the state to carry out its obligations to meet the people's needs, through the delegation of its implementation to BUMN. At this writing, it is shown about the development and implementation of natural monopolies by BUMN in Indonesia.